THE SITUATION OF THE MODERN INGUSH WOMAN - Evloeva, Liana Maisovna (History, Archeology and Ethnography of the Caucasus, 2021)
To date, there are no separate studies of the status of a modern Ingush woman, her position in society, etc. At the same time, there are paragraphs, fragments in the works of Ingush researchers, as well as a small number of articles published by Ingush scientists in Russian scientific journals and republican newspapers.This article attempts to partially fill this gap - to describe the place and role of women in modern Ingush society, which have undergone significant transformations due to objective reasons (the collapse of the USSR, the Ossetian-Ingush conflict, the formation of the Ingush Republic , the strengthening of religious sentiments of the population, globalization processes, etc.)In this work, we examined such topical issues as psychological and physical violence in the family, the reasons for this phenomenon in Ingush families; introduced new ethnographic information obtained by us during the research in 2018-2020.We concluded that the topic of violence is relevant not only for the Ingush region, but also for the country as a whole. The lowering of the status of the Ingush was not influenced by Islam, as many authors wrote about, but, rather, by an incorrect interpretation of the norms of religion. Today, women in Ingushetia are becoming more and more independent, as they have become economically independent. Despite this, traditional attitudes continue to play an important role in the life of the Ingush. This is evidenced by the fact that women prefer to marry as a second wife to an Ingush, rather than the first to a person of a different nationality.
Keywords: Ingushka; woman; position of a woman; Ingushetia; domestic violence; polygamy; Islam.